A rare case of long-term joint swelling caused by pigmented villonodular synovitis in a 3-year-old girl: a case report - Liu, Yang; Liang, Shaohua; Wang, Wen (Frontiers in Surgery, 2023)
The clinical symptoms of pigmented villonodular synovitis (PVNS) are usually insidious and non-specific; therefore, delays in diagnosis and treatment are common. Here, we describe a case of a 3-year-old patient presenting with long-term joint swelling to highlight the significance of considering PVNS as a differential diagnosis in children to prevent misdiagnosis and ensure early treatment. After arthroscopic debridement, our patient had a favorable clinical outcome and was free of recurrence.